2018
DOI: 10.1080/08989621.2018.1435280
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance or decline of requests to review manuscripts: A gender-based approach from a public health journal

Abstract: Peer review in the scientific publication is widely used as a method to identify valuable knowledge. Editors have the task of selecting appropriate reviewers. We assessed the reasons given by potential reviewers for declining a request to review, and the factors associated with acceptance, taking into account the difference in the sex of the reviewer. This is a descriptive study of the review requests from a public health journal (Gaceta Sanitaria) with an enforced gender policy. The dependent variables were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Peer review, pivotal to the publication process, is under increasing pressure and prone to many potential biases,891011 but the extent of these biases has been less investigated than other areas of the publication process as most peer review is done anonymously and reviews are not usually in the public domain 1213. Some studies have analysed the selection of peer reviewers and their response to invitations to review submissions to biomedical journals; however, as this information is confidential, these studies have largely been done within single journals and may not be representative beyond their communities 141516. Analyses of published peer reviews and public acknowledgment statements to named reviewers of biomedical journals have shown gender and geographical bias in the contributions 17181920…”
Section: Introductionmentioning
confidence: 99%
“…Peer review, pivotal to the publication process, is under increasing pressure and prone to many potential biases,891011 but the extent of these biases has been less investigated than other areas of the publication process as most peer review is done anonymously and reviews are not usually in the public domain 1213. Some studies have analysed the selection of peer reviewers and their response to invitations to review submissions to biomedical journals; however, as this information is confidential, these studies have largely been done within single journals and may not be representative beyond their communities 141516. Analyses of published peer reviews and public acknowledgment statements to named reviewers of biomedical journals have shown gender and geographical bias in the contributions 17181920…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most commonly cited explanation is reviewer fatigue: with increasing pressure to publish and a rapidly increasing universe of political science journals, academics are inundated with invitations. Research on this issue, however, has generally found that the challenge has more to do with overall workload than with review requests themselves (Breuning et al 2015;Domínguez-Berjón et al 2018;Fox, Albert, and Vines 2017;Willis 2015). In a survey of American Political Science Association (APSA) members in 2013, for example, Djupe (2015) found that only 10% of respondents were doing more than one review each month.…”
Section: Introductionmentioning
confidence: 99%
“…Early career researchers with less experience may not be appropriate reviewers for specific research questions, and late career researchers may be over-targeted to conduct reviews or biased [15]. Gender bias issues have also been found to affect peer review rates [16]. These are factors that may be hard to quantify, which is why focusing on determining the number of reviews required by the peer review system may help researchers by offering a means to improve the peer review system, and provide a basis for research on the second more complex aspect discussed here.…”
Section: Introductionmentioning
confidence: 99%